2016
DOI: 10.1111/jch.12913
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness in Treated Hypertensive Patients With White‐Coat Hypertension

Abstract: Arterial stiffness, assessed through pulse wave velocity (PWV), independently predicts cardiovascular outcomes. In untreated persons, white‐coat hypertension (WCH) has been related to arterial stiffness, but data in treated patients with WCH are scarce. The authors aimed to determine a possible association between WCH and arterial stiffness in this population. Adult treated hypertensive patients underwent home blood pressure monitoring and PWV assessment. Variables associated with PWV in univariable analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Noteworthy, in the present study the systolic and diastolic BP values were 13–16 and 16–17 mmHg lower, respectively, during the haemodynamic laboratory measurements than in the office measurements. This resembles the white-coat effect in hypertension, which has been related to large arterial stiffness in both untreated 52 and treated hypertensive patients 53 . Out-of-office BP monitoring provides better assessment of overall BP and response to treatment in patients with white-coat hypertension 54 .…”
Section: Discussionmentioning
confidence: 63%
“…Noteworthy, in the present study the systolic and diastolic BP values were 13–16 and 16–17 mmHg lower, respectively, during the haemodynamic laboratory measurements than in the office measurements. This resembles the white-coat effect in hypertension, which has been related to large arterial stiffness in both untreated 52 and treated hypertensive patients 53 . Out-of-office BP monitoring provides better assessment of overall BP and response to treatment in patients with white-coat hypertension 54 .…”
Section: Discussionmentioning
confidence: 63%
“…erefore, arterial elasticity and function are used as a variety of cardiovascular risk factors for subclinical vascular lesions [8][9][10]. Recently, it has been demonstrated that arterial stiffness is another important risk factor that is independent of other cardiovascular risk factors and is considered to be an alternative endpoint of cardiovascular disease, and is associated with the morbidity and mortality of cardiovascular disease [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the present measurements performed in supine position under quiet standardized laboratory conditions did not uncover any significant differences in peripheral or central BP between the PUA quartiles. Previously, white-coat hypertension was reported to be independently associated with higher large arterial stiffness in treated hypertensive patients [ 49 ]. Furthermore, when evaluated using the ratio of pulse pressure to stroke volume, higher arterial stiffness was also significantly related to the white-coat effect in 2778 hypertensive patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%